Vibratory stimulus to the masseter muscle impairs the oral fine motor control during biting tasks. Issue 3 (July 2019) - Kumar, Abhishek; Tanaka, Yuto; Takahashi, Kazutaka; Grigoriadis, Anastasios; Wiesinger, Birgitta; Svensson, Peter; Trulsson, Mats
Abstract: Purpose: To investigated the effect of vibratory stimulus on masseter muscles during oral fine motor biting tasks. Methods: Sixteen healthy individuals (age: 24.5 ± 2.4 years) participated in experiment I during which the participants were asked to "hold and split" half a roasted peanut placed on a force transducer with their front teeth. The participant performed ten series with ten trials of the "hold and split" behavioral task while vibratory stimulus was applied on the masseter muscle every alternate series. Further, fourteen participants participated (age: 25.2 ± 4.8 years) in experiment II during which they performed a series each of the behavioral task at baseline, an adjusted baseline without and with vibration as well as with and without visual feedback. Hold and split forces along with the variability of hold force and duration and force rate during the split were measured. Results: The results of the study showed an increase in the magnitude of the hold force (P = 0.002), force rate during the split (P < 0.001) and a significant decrease in the duration of split (P < 0.001) due to the vibratory stimulus. However, there was no significant effect of the vibratory stimulus on the variability of hold forces (P = 0.879) or mean split force (P = 0.683) during the "hold and split" behavioral task. The results of experiment II also showed an increase in hold force due to the vibratory stimulus (P < 0.001). Conclusions: Vibratory stimulus to the masseter muscles impairs the oral force control during a standardized biting task and provide further insight into the sensorimotor regulation of the masticatory system.